PERILAKU TIDAK MEMILIH MASYARAKAT DESA DI KECAMATAN MANDAU DALAM PILKADA KABUPATEN BENGKALIS TAHUN 2015 ( STUDI KASUS DESA BUMBUNG DAN DESA PAMESI) - Hasugian, Andi Saputra; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Behavior does not choose interesting to study because it is showing the public outcry over what happens in political activities that took place. This study describes the behavior did not vote in the two villages of Bumbung and Village Pamesi. This study refers to main village and village expansion highest level of behavior is not chosen in the District Saber.This study used qualitative methods and was conducted at the Bumbung and Pamesi Village, District Mandau, Bengkalis 2015. This research use informants as sources of information objects that aims to achieve mastery in getting information. Data used in this study are primary data and secondary data obtained through direct observation and interviews with informants. Analysis of the data in the study was done descriptively to explain the data in a systematic and objective so as to produce factual information, real-time and accurate.Based on the results of the study found the following: Awareness and trust are the main thing in using the right to vote or participate in the elections, it should be emphasized to the public that the vote is important because it involves who will lead their area the next five years and are very influential for the policy to be changed and that will be made by the elected regional head. The causes of the villagers and village Bumbung Pamesi not choose that administrative problems, not in place when the election, do not know the candidate, lack of socialization of the organizers and of the candidates will be selected and prefer to work rather than having to choose saaat elections. This shows the high and various behavioral factors did not choose in the Village and Village Bumbung Pamesi. So it takes people who are aware and believe it is a choice that the elections means changes carrier for the progress of a region. The role of the organizers is Bengkalis district commissioner is expected to reduce the behavior did not choose in Bengkalis and establish people's confidence that they as organizers were able to hold elections in a fair, honest, free and confidential. Election Commission as a service provider must be able to demonstrate a neutral attitude towards all candidates are ahead in the election so that people trust and believe there is no manipulation in the electoral process.Keywords: Non voting behavior, election